Pengaruh Tamoxifen Terhadap Jantung Tikus Dua Bulan Pasca Ovariektomi - BONDAN P.P., Ade ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The use of tamoxifen as estrogen replacement therapy showed diverse effects on several organs. Therefore, this research was conducted to study the effect of tamoxifen on heart weight, macroscopic and histopathological figure of the ovariectomized rat heart. Eight of female rats at ±2 months of age were divided into 2 groups of 4 (group A and group B). Group A was ovariectomized without giving tamoxifen and group B was ovariectomized with administration of tamoxifen (10 mg/kg/day). Rats were fed standard diet and water was given ad libitum. Treatment was done for 2 months after ovariectomy. The results showed that there was no significant difference (P>0.05) between the heart weight/100g body weight of ovariectomized rat without tamoxifen (0.42±0.06g) and with tamoxifen (0.48±0.08g). Macroscopically, heart of ovariectomized rat without and with tamoxifenwere looked normal. Histopathologically, cardiac muscle was appeared normal, branched fibers of cardiac muscle, connective tissue was clearly visible, the nucleus of cardiac muscle cells was located in the middle and surrounded by pale cytoplasm. Aorta was also showed a normal structure in the tunica intima, tunica media, and tunica adventitia, meanwhile, endothelial wall was showed no damage, rips, LDL accumulation, and blockages. In conclusion, administration of tamoxifen for 2 months after ovariectomy had no effect on heart weight and macroscopic and histopathological figure of the heart and aorta.